STRATEGI BISNIS STARTUP DENGAN PENDEKATAN BUSINESS MODEL CANVAS - Citra, Kezia; Windy Wulandari, Agri; Oktapiyana, Oktapiyana; Priskila, Priskila (Jurnal Pariwisata Tawangmangu, 2023)
A start-up is a start-up or start-up that is being developed. Bagomez is a culinary start-up founded by students of the Bukit Pengharapan Tawangmangu Christian Institute of Technology and Business study program that produces and sells fried meatballs with chicken meat raw materials. Bagomez as a start-up business is still experiencing stagnansi and has not produced optimal performance. It aims to find the right business strategy for Bagomez's start-up business. The method carried out is to use a business model canvas approach through interviews and FGDs (focus group discussions) conducted with sister companies. The results showed that the components contained in BMC were used as Bagomez's business strategy as a start-up, which were interrelated, especially in the value proposition, customer segment, revenue stream, channel, and key activities components.